Immune response to JC virus T antigen in patients with and without colorectal neoplasia - Butcher, Lindsay D (Gut Microbes, 2014)
JC virus (JCV) is a polyomavirus that infects approximately 75% of the population and encodes a T antigen (T-Ag) gene, which is oncogenic and inactivates the p53 and pRb/p107/p130 protein families. Previous work in our lab has identified the presence of T-Ag in colorectal neoplasms. While JCV remains in a latent state for the majority of those infected, we hypothesized that a disturbance in immunological control may permit JCV to reactivate, which may be involved in the development of colorectal neoplasia. Our aim was to determine the cell mediated immune response to JCV T-Ag, and determine if it is altered in patients with colorectal adenomatous polyps (AP) or cancers (CRC). Peripheral blood mononuclear cells (PBMCs) isolated from the blood of patients undergoing colonoscopy or colorectal surgery were stimulated by a peptide library covering the entire T-Ag protein of JCV. Cytokine production and T cell proliferation were evaluated following T-Ag stimulation using Luminex and flow cytometry assays. JCV T-Ag peptides stimulated secretion of IL-2, which induced T cell expansion in all three groups. However, stronger IL-10 and IL-13 production was seen in patients without colorectal neoplasms. IP-10 was produced at very high levels in all groups, but not significantly differently between groups. Most patients exhibited CD4(+) and CD8(+) T cells in response to stimulation by the T-Ag clusters. The combination of IL-2 and IP-10 secretion indicates the presence of T-Ag-specific Th1 cells in all patients, which is higher in patients without carcinoma.